2020
DOI: 10.2174/1874944502013010447
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Management of HIV and NCDs within the Primary Health Care in the South African Context: A Comprehensive Literature Review

Abstract: Introduction Low and middle-income countries, including South Africa, are facing a challenge of the dual burden of chronic communicable and non-communicable diseases, which again pose a challenge to the improvement of patients’ clinical outcomes in the primary health care facilities. The introduction of innovative intervention to address the dual burden in South Africa created a challenge on nurses working at primary health care facilities to acquire a new set of skills to improve patients’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…From the literature review, we have found that there is no reporting tool for integrated management of HIV and NCDs. However, there are separated reporting data tools for HIV and NCDs [10]. In addition, we have observed that there is an integration of communicable diseases, such as HIV and TB are reported together.…”
Section: Step 1: Research Problem Identificationmentioning
confidence: 99%
“…From the literature review, we have found that there is no reporting tool for integrated management of HIV and NCDs. However, there are separated reporting data tools for HIV and NCDs [10]. In addition, we have observed that there is an integration of communicable diseases, such as HIV and TB are reported together.…”
Section: Step 1: Research Problem Identificationmentioning
confidence: 99%